Uso de agregados reciclados de concreto em substituição ao agregado graúdo natural na produção de concretos estruturais - Rauber, Renan (2024)
The construction industry generates a lot of waste due to waste in conventional methods. In 2021, 48.375 million tons of waste were collected in Brazil, mostly ceramic and cement (concrete and mortar). Concrete, produced in concrete batching plants, has the benefit of standardization and consequent reliability of the mixtures, verified according to the design parameters. However, the leftover material generates solid waste destined for landfills. In a plant with a monthly production of 3 thousand m³, it is estimated that 2.5 to 3 m³/day of waste is generated, around 7 tons per day in a plant in western Paraná alone. This work uses concrete waste as a substitute for natural coarse aggregates (gravel) in structural concrete. Concrete waste from a plant in Toledo/PR was found and crushed, and aggregates with a maximum characteristic dimension of 19 mm were found. The replacement rates of natural aggregates by recycled aggregates were 5%, 10%, 15%, 20%, 50%, 75% and 100%. Their observations were confirmed through mechanical and durability tests. Tests were performed on particle size, quantity of powdery material, water collection, cone slump, uniaxial analysis, diametrical tensile strength, ultrasonic pulse velocity and carbonation. The concretes were dosed according to the IPT/USP method, relating cement consumption, compressive strength and slump, thus providing diagrams in different replacement percentages, establishing a basis for the use of the aforementioned concrete mixes by concrete plants, and their respective characteristics mentioned above. The recycled concrete aggregate proved to be more lamellar, which may have influenced characteristics such as compressive strength. The slump was in the range of 160±20 mm and therefore, all mixtures with replacement required the use of additives to achieve slump. The specific mass of the concrete in the fresh state was influenced, being reduced at higher replacement levels. In compressive strength, the poor mix showed an increase in resistance up to 20% replacement, with subsequent reduction. For the rich mix, there was a reduction in all mixes, however, not greater than 29.4%. In the intermediate mix, the values oscillated between increased and reduced strength, not exceeding a 21% reduction. The quality of the concrete was very poor for the mix with 50% replacement in the lean mix. The others had ultrasonic pulse velocities above 2.98 km/s. The carbonation depth on the surface had a maximum carbonation value with 20% replacement and was 18 mm, however, the recycled aggregates are more porous, generating fronts that are more susceptible to attacks by carbon dioxide. The 100% replacement generated concretes with a significant reduction in strength for the three mixes, and for the lean mix, this occurred after 20% replacement. For the intermediate and rich mixes, the reduction became less significant up to 75%. Thus, the minimization of discarded waste, the reduction of CO2 emissions and the decrease in the extraction of raw material make the replacements environmentally positive.